Kesepian pada Mahasiswa: Bagaimana Peran Sosial Adjustment dan Pet Attachment ? - Harjanto, Ade Pradipta; Sukiatni, Dwi Sarwindah; Kusumandari, Rahma (JIWA: Jurnal Psikologi Indonesia, 2023)
Every year when entering the new school year there are always students from outside the region or from their place of origin to pursue proper education in big cities. Obstacles and challenges faced by students such as loneliness are often experienced by overseas students, as well as factors that cause such as social adjustment. In addition, attachment to pets is also a factor in loneliness, therefore this study aims to determine the relationship between social adjustment and pet attachment with loneliness in overseas students in Surabaya. The design in this study used questionnaire information collection, while the subjects in this study were overseas students in the Sukolilo sub-district of Surabaya city, totaling 100 people. In this study using correlational qualitative methods. The results in this study show that there is no relationship between social adjustment and loneliness and there is a relationship between pet attachment and loneliness in overseas students in Surabaya. The conclusion in this study is that the first hypothesis is rejected and the second hypothesis is accepted, while the third hypothesis cannot be tested because it does not meet the prerequisite test. Setiap tahun ketika memasuki tahun ajaran baru selalu ada mahasiswa yang dari luar daerah atau mernatau dari tempat asal untuk menempuh pendidikan yang layak di kota-kota besar. Rintangan dan tantangan yang dihadapi oleh mahasiswa seperti kesepian kerap kali dialami oleh mahasiswa rantau, adapun faktor yang menyebabkan seperti penyesuaian sosial. Selain itu kelekatan dengan hewan peliharaan juga menjadi faktor dalam kesepian, maka dari itu penelitian ini bertujuan untuk mengetahui hubungan antara social adjustment dan pet attachment dengan kesepian pada mahasiswa rantau di Surabaya. Desain dalam penelitian ini menggunakan pengumpulan informasi kuesioner, adapun subjek dalam penelitian ini adalah mahasiswa rantau yang ada di kecamatan Sukolilo kota Surabaya yang berjumlah 100 orang. Dalam penelitian ini menggunakan metode kualitatif korelasional. Hasil dalam penelitian ini menunjukan tidak terdapat hubungan antara social adjustment dengan kesepian dan terdapat hubungan antara pet attachment dengan kesepian pada mahasiswa rantau di Surabaya. Kesimpulan dalam penelitian ini bahwa hipotesis pertama ditolak dan hipotesis kedua diterima, adapun hipotesis ketiga tidak dapat diuji karena tidak memenuhi uji prasyarat.